2022
DOI: 10.1177/17562872221079473
|View full text |Cite
|
Sign up to set email alerts
|

Surgery improves survival in bladder signet-ring cell carcinoma-a population-based study

Abstract: Objectives: The purpose of this study is to determine the therapeutic value of surgery in individuals with urinary bladder signet ring cell carcinoma (SRCC). Surgery has not been examined as a prognostic factor for urinary bladder cancer (SRCC). Materials and Methods: Using the Surveillance, Epidemiology, and End Results program (SEER), patients with urinary bladder SRCC who presented from 1975 to 2018 were included in a retrospective study. The effect of surgical therapy on cause-specific survival (CSS) and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…The following limitations of this study should be considered. First, there was selection bias in this study, for being a retrospective analysis [ 14 ]. Second, due to the limitations of the SEER database, the concrete chemotherapy regimen and the details of local regional recurrence data were not available, to impact the survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The following limitations of this study should be considered. First, there was selection bias in this study, for being a retrospective analysis [ 14 ]. Second, due to the limitations of the SEER database, the concrete chemotherapy regimen and the details of local regional recurrence data were not available, to impact the survival.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, A total of 588 patients were enrolled in the study. The histologic type was classified using the International Classification of Disease for Oncology, 3rd Edition (ICD-O-3), and the tumor stage categorized using Seer historic stage [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Cazier et al, on the other hand, demonstrated that these genes are extremely carcinogenic in ordinary bladder cancer 27 . Finally, by using the last updated edition of the SEER database, the survival comparison between SRCC and UC revealed that ordinary urothelial carcinoma has a greater survival rate, which will explain the difference in gnomic characteristics and driving pathways between the two diseases 37–39 …”
Section: Discussionmentioning
confidence: 99%
“…27 Finally, by using the last updated edition of the SEER database, the survival comparison between SRCC and UC revealed that ordinary urothelial carcinoma has a greater survival rate, which will explain the difference in gnomic characteristics and driving pathways between the two diseases. [37][38][39] But there are limitations to our analysis. First, due to the rarity of the disease, only a small number of cases were available for analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery operation and lymph nodes removal are considered protective prognostic factors in prolonged patients' survival. Alradhi et al [ 22 ] reported that surgery served as a significant independent protective factor for PSRCC survival. However, whether surgery should be the most appropriate surgical modality was not further analyzed.…”
Section: Discussionmentioning
confidence: 99%